Comparative study of uterine repair during caesarean section: exteriorization repair versus in-situ repair - Priya, Lakshmi; P., Reddi Rani; B, Lopamudra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cesarean section is one of the most common major obstetrical operation performed worldwide and the rates of cesarean section are increasing. It is associated with both intra-operative and post-operative complications. Many variations in surgical methods have been devised to decrease the adverse effects and morbidity. One such method is technique of uterine repair after delivery of the fetus and placenta by exteriorizing the uterus or in-situ repair. Methods: A prospective comparative study was conducted in the department of Obstetrics and Gynecology at MGMCRI Pondicherry over 18 months from March 2015 to August 2016. Two hundred women undergoing caesarean section were assigned to 2 groups. Group 1 (Exteriorization) 100 women and Group 2 (In-situ repair) 100 women. Intra-op and post-operative complications were assessed in both groups and compared. Results: There was no significant difference between the two groups with regard to age, parity, gestational age and type of cesarean section. There was no significant difference between two groups with regard to fall in Hb, operating time, mean drop in pulse rate and blood pressure, nausea, vomiting and intra-op pain. There was significant difference in blood loss during surgery in in-situ repair, P value was <0.001 highly significant and also statistically significant increase in transfusion rates in in-situ group with a p value of 0.038. Postoperative complications like febrile morbidity was significantly more in in-situ repair P=0.046. There was no significant difference in other variables like urinary tract infection, surgical site infection, endometritis and hospital stay. Conclusions: Both techniques are accepted methods of uterine repair. Technique of repair depends on surgeon’s choice and clinical situation. Exteriorization repair is a valid option with no significant increase in morbidity compared to In-situ repair especially in cases where exposure of lower uterine segment is difficult, there is extension of incision and difficulty in achieving hemostasis.